Overexpression of mineralocorticoid receptors does not affect memory and anxiety-like behavior in female mice - Kanatsou, Sofia; Kuil, Laura E.; Arp, Marit; Oitzl, Melly S.; Harris, Anjanette P.; Seckl, Jonathan R.; Krugers, Harm J.; Joels, Marian (Frontiers in Behavioral Neuroscience, 2015)
Mineralocorticoid receptors (MRs) have been implicated in behavioral adaptation and learning and memory. Since—at least in humans—MR function seems to be sex-dependent, we examined the behavioral relevance of MR in female mice exhibiting transgenic MR overexpression in the forebrain. Transgenic MR overexpression did not affect contextual fear memory or cued fear learning and memory. Moreover, MR overexpressing and control mice discriminated equally well between fear responses in a combined cue and context fear conditioning paradigm. Also context-memory in an object recognition task was unaffected in MR overexpressing mice. We conclude that MR overexpression in female animals does not affect fear conditioned responses and object recognition memory.